Роль соціально-емоційного навчання під час здобуття освіти - Куліченко, Алла Костянтинівна; Kulichenko, A. K. (My University, 2024)
У тезах увагу зосереджено на соціально-емоційному навчанні, яке є важливим в сучасній освіті, оскільки сприяє розвитку навичок управління емоціями та формуванню сприятливого освітнього середовища. The abstract highlights the significance of social and emotional learning within contemporary education, emphasizing its role in developing emotional management skills and fostering a conducive learning atmosphere.
Role of Social and Emotional Learning in Education
Keywords: навчання; виховання; соціальний та емоційний розвиток; емоції; соціум; education; upbringing; social and emotional development; emotions; society